1996
DOI: 10.1002/(sici)1097-0142(19960215)77:4<778::aid-cncr25>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory myofibroblastic tumor (Inflammatory pseudotumor): DNA flow cytometric analysis of nine pediatric cases

Abstract: The present data indicate that flow cytometry identifies aneuploidy (hyperdiploidy) in approximately half of the cases of inflammatory myofibroblastic tumors. This feature appears to reflect a more aggressive biologic behavior. In addition to the reported cytogenetic abnormalities, our data suggest that inflammatory myofibroblastic tumor, generally considered a benign reactive inflammatory process, may evolve as a distinct, potentially malignant, lesion. Therefore, flow cytometric DNA analysis is a suitable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
67
0
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(72 citation statements)
references
References 28 publications
1
67
0
4
Order By: Relevance
“…14 Birelli and coworker in their study found that around 50% of extrapulmonary IMFT in pediatric age group are aneuploid. 18 Meis and Enzinger in their study of 38 cases found to have 3 patients with distant metastasis and 8 had local invasion. 19 Reports are there in literature supporting the neoplastic nature of the tumor.…”
Section: Discussionmentioning
confidence: 88%
“…14 Birelli and coworker in their study found that around 50% of extrapulmonary IMFT in pediatric age group are aneuploid. 18 Meis and Enzinger in their study of 38 cases found to have 3 patients with distant metastasis and 8 had local invasion. 19 Reports are there in literature supporting the neoplastic nature of the tumor.…”
Section: Discussionmentioning
confidence: 88%
“…Inflammatory myofibroblastic tumor is a rare benign solid tumor with an obscure etiology (4,5). Despite an apparently benign morphological nature, some cases of IMT have been reported to have a malignant clinical course, such as a locally aggressive growth and a tendency to recur after a complete resection (5).…”
Section: Discussionmentioning
confidence: 98%
“…Despite an apparently benign morphological nature, some cases of IMT have been reported to have a malignant clinical course, such as a locally aggressive growth and a tendency to recur after a complete resection (5). It is usually difficult to confirm the accurate diagnosis before operation (6, 7).…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings is suggestive of neoplasm because of the clonal chromosomal abnormalities. The chromosomal rearrangements involving the ALK receptor tyrosine-kinase locus region (chromosome band 2p23), or DNA aneuploidy in IMT [9,10]. In our case this chromosomal study was not done.…”
Section: Discussionmentioning
confidence: 99%